PENGARUH FAKTOR DEMOGRAFI DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI SAHAM - Nggadas, Maria Virginia; Candraningrat, Ica Rika (Buletin Studi Ekonomi; VOLUME.28.NO.01.TAHUN.2023, 2023)
This study aims to examine the effect of demographic variables consisting of gender, age, educational background, income level, marital status and professional, as well as financial literacy consisting of dimensions of financial attitudes, financial behavior and financial knowledge on stock investment decisions in the Indonesian Stock Exchange. The results of multiple linear regression tests that have been tested using IBM SPSS Statistic software for Windows version 22 found that demographic factors consisting of gender, age, educational background, income level, marital status and profession have no effect on investment decisions, while the financial literacy variable which consists dimensions of financial attitudes, financial behavior and financial knowledge affect stock investment decision making.